2018
DOI: 10.2337/dc18-0165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Empagliflozin on Liver Fat in Patients With Type 2 Diabetes and Nonalcoholic Fatty Liver Disease: A Randomized Controlled Trial (E-LIFT Trial)

Abstract: When included in the standard treatment for type 2 diabetes, empagliflozin reduces liver fat and improves ALT levels in patients with type 2 diabetes and NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
400
3
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(431 citation statements)
references
References 39 publications
18
400
3
10
Order By: Relevance
“…Ito et al previously reported that treatment with ipragliflozin, another SGLT2 inhibitor, reduced hepatic steatosis, which they evaluated from the liver‐to‐spleen attenuation ratio on CT. Very recently, Kuchay et al also demonstrated that empagliflozin reduced liver fat content, evaluated by MRI‐derived proton density fat fraction in patients with type 2 diabetes and NAFLD. Magnetic resonance elastography or MRI‐derived proton density fat fraction has a better diagnostic accuracy for assessing significant fibrosis than transient elastography, although the former techniques are expensive and time‐consuming to implement in clinical practice for screening liver fibrosis .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Ito et al previously reported that treatment with ipragliflozin, another SGLT2 inhibitor, reduced hepatic steatosis, which they evaluated from the liver‐to‐spleen attenuation ratio on CT. Very recently, Kuchay et al also demonstrated that empagliflozin reduced liver fat content, evaluated by MRI‐derived proton density fat fraction in patients with type 2 diabetes and NAFLD. Magnetic resonance elastography or MRI‐derived proton density fat fraction has a better diagnostic accuracy for assessing significant fibrosis than transient elastography, although the former techniques are expensive and time‐consuming to implement in clinical practice for screening liver fibrosis .…”
Section: Discussionsupporting
confidence: 87%
“…We demonstrated significant improvement in CAP (an indicator of hepatic steatosis) in the dapagliflozin group after 24 weeks of treatment, while there was no improvement in the control group, and the percent reduction in CAP from baseline to 24 weeks was significantly larger in the dapagliflozin group than in the control group. There has only been two previous prospective investigations into the effect of SGLT2 inhibitors on hepatic steatosis that employed imaging methods such as CT and MRI . In the present study, we investigated the effect of dapagliflozin by measuring CAP, a new quantitative index of hepatic steatosis .…”
Section: Discussionmentioning
confidence: 97%
“…In humans, 2 pooled analyses reported a decrease in plasma aminotransferases with canagliflozin treatment that correlated with the magnitude of body weight loss. A reduction in ALT and/or IHTG has been reported in small, open‐label studies of 5‐ to 6‐months duration with luseogliflozin, ipragliflozin, and empagliflozin, associated with reductions in BMI, visceral fat, and HbA1c. Tobita et al showed additional improvement in histology in a small, uncontrolled study in patients with biopsy‐proven NASH .…”
Section: Discussionmentioning
confidence: 86%
“…Comments: The above studies only included patients with diabetes, and none of them involved histological assessment of outcomes. In the study by Seko et al alcohol intake was not regulated, and patients with an ALT/AST >2.5 × the upper limit of normal were excluded. Neither of the RCTs was placebo‐controlled, and participants were concurrently taking other medications that could have potentially impacted outcomes. …”
Section: Modulation Of Ir In Nafldmentioning
confidence: 99%